(untitled) (Third Sector Social Economic Review, 2023)
In recent years, the use of information and communication technologies has increased to help global businesses in transition process of activities to digital environment. Employees have to use many technologies. With these developments, employees can experience the phenomenon of technostress described as the dark side of technology. Technostress occurs as a result of imbalance between individual and technology environment in organizations. Globalization and technological developments increase workaholism. Workaholism is explained as individual’s intense interest and feeling forced to work due to internal pressures. The study aims to examine the relationships between the technostress perception and the level of workaholism of employees in public and private sectors, to determine whether concepts differ regarding demographic variables. The data from 202 participants obtained by applying face-to-face and online survey methods within the scope of quantitative research design were analyzed through SPSS 22 by applying ANOVA, descriptive, correlation, regression and factor analyses. According to the results, significant and positive relationships emerged between employee’s technostress perceptions and workaholism levels. Besides technostress differed in terms of gender, workaholism differed in terms of marital and educational status. The study aims to contribute to knowledge in the literature. Keywords: Technostress, Workaholism, Public sector, Private sector, Quantitative research